Scent as a Strategic Element of Hotel Design to enhance Guest Experience - Sanawete Sirirat; Chotewit Pongsermpol; Chumporn Moorapun (My University, 2025)
Scent has become a key marketing tool in the hotel industry, significantly enhancing the guest experience. This study investigates the impact of scent on guest perceptions and satisfaction in hotels across five regions of Thailand. Utilizing a mixed-methods approach, data were collected from 1,000 online reviews mentioning scent-related factors from 25 hotels. Thematic content analysis identified 15 scent categories, classified into Pleasant & Fresh, Natural & Woody, Luxury & Perfume, and Unpleasant Scents, followed by Chi-square tests to assess their significance.Findings show that floral and herbal scents notably boost guest satisfaction, with floral scents being prevalent in lobbies, guest rooms, and spas, while herbal scents are common in spas and wellness centers. Conversely, unpleasant odors, such as dampness and smoke, negatively impact guest experiences, particularly in hallways and bathrooms. This study highlights the importance of effective scent management in hotels to enhance guest satisfaction and encourage repeat visits.
Keywords: Diverse Aspects of Tourism Research